ANALYSIS INDUSTRY RIVALRY AND COMPETITION : ANALISIS PERSAINGAN KOMPETITIF PERUSAHAAN E-COMMERCE SHOPEE DENGAN MENGGUNAKAN METODE PORTER’S FIVE FORCES - Adi Neka Fatyandri; Janes Tan; Junes tin; Putri Surya Sri Rahayu; Andriani Fahira; Chairunisa Aj Reqha (Politeknik Bisnis Indonesia, 2023)
This analysis is to analyze competitive rivalry against Shopee companies. In this analysis using descriptive analysis method and using a qualitative approach. Competitive competition analysis using Porter's Five Forces method is a strategic framework used to evaluate the attractiveness and intensity of competition in a particular industry or market. In the context of a Shopee company, this analysis can provide insight into the factors influencing Shopee's position in the e-commerce market and identify opportunities and challenges faced by the company. Keywords: Business strategy, Competitive competition, Shopee, Potter's Five Forces